2016
DOI: 10.5483/bmbrep.2016.49.9.094
|View full text |Cite
|
Sign up to set email alerts
|

Precise assembly and regulation of 26S proteasome and correlation between proteasome dysfunction and neurodegenerative diseases

Abstract: Neurodegenerative diseases (NDs) often involve the formation of abnormal and toxic protein aggregates, which are thought to be the primary factor in ND occurrence and progression. Aged neurons exhibit marked increases in aggregated protein levels, which can lead to increased cell death in specific brain regions. As no specific drugs/therapies for treating the symptoms or/and progression of NDs are available, obtaining a complete understanding of the mechanism underlying the formation of protein aggregates is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 101 publications
(153 reference statements)
1
26
0
Order By: Relevance
“…In a second example, complex-centric analysis in combination with manual refinement identified early and late assembly intermediates on the path toward the 20S proteasome particle based on defined co-elution of the respective assembly chaperones. Strikingly, the early and late intermediary complexes assigned (early: a1/a3/a4/ a5/a7, late: a1-7/b2/b3/b6/b7) collide with current models of the temporal order of subunit assembly (Hirano et al, 2008;Im & Chung, 2016; for a graphical summary, see Fig 6B, lower panel). Current models entail early a-ring intermediates lacking subunits a3 and a4 (Hirano et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…In a second example, complex-centric analysis in combination with manual refinement identified early and late assembly intermediates on the path toward the 20S proteasome particle based on defined co-elution of the respective assembly chaperones. Strikingly, the early and late intermediary complexes assigned (early: a1/a3/a4/ a5/a7, late: a1-7/b2/b3/b6/b7) collide with current models of the temporal order of subunit assembly (Hirano et al, 2008;Im & Chung, 2016; for a graphical summary, see Fig 6B, lower panel). Current models entail early a-ring intermediates lacking subunits a3 and a4 (Hirano et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…In support of this possibility, recent studies (55,56) demonstrated the phosphorylation of several components (e.g., Rpn1p, Rpt2p, Rpt3p, Rpt5p, and Rpt6p) of the 19S proteasome subcomplex. Such phosphorylation has been implicated in facilitating the ATPase activity of the 19S proteasome subcomplex and its assembly (55,57) and hence function (since previous studies demonstrated the role of the 19S ATPases in stimulation of the interaction between activator and coactivator [1,14,37,44]). Intriguingly, changes of phosphorylation of several components (e.g., Rpt1p, Rpt2p, Rpt3p, Rpt5p, and Rpn1p) of the 19S proteasome subcomplex were observed following rapamycin inhibition of TOR (58).…”
Section: Discussionmentioning
confidence: 99%
“…Since 19S proteasome subcomplex promotes the targeting of the coactivator SAGA (14,37,44), PIC formation at the SAGA-dependent genes would also be impaired following TOR inhibition by rapamycin (as TOR promotes phosphorylation of the 19S proteasome subcomplex and its function [55,57,58]). Indeed, we found that PIC formation at the promoter of the SAGA-regulated, but NuA4 KAT-independent, ADH1 gene (42) was decreased following TOR inhibition by rapamycin ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation of CP and phosphorylation of both CP and RP subunits were found to affect proteasome activity (31), while phosphorylation of the Rpt6 ATPase subunit of RP was found to have a role in proteasome assembly (31,32). Recently, more than 345 PTMs of 11 different types were detected on the 26S proteasome (33), however because most of the obtained PTM data is quite novel and originates from large proteomics studies, their roles are still predominantly unknown (34).…”
Section: Graphical Abstractmentioning
confidence: 99%